6*3+3=3(3)+12

Simple and best practice solution for 6*3+3=3(3)+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6*3+3=3(3)+12 equation:


Simplifying
6 * 3 + 3 = 3(3) + 12

Multiply 6 * 3
18 + 3 = 3(3) + 12

Combine like terms: 18 + 3 = 21
21 = 3(3) + 12

Multiply 3 * 3
21 = 9 + 12

Combine like terms: 9 + 12 = 21
21 = 21

Add '-21' to each side of the equation.
21 + -21 = 21 + -21

Combine like terms: 21 + -21 = 0
0 = 21 + -21

Combine like terms: 21 + -21 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 10x+17=2x+15 | | 5x.8=0 | | 1x+10=5x+10 | | -5x-11=44 | | t^2=2+2t | | x=-3+3y | | 10y^2-10=0 | | t^2-2t-2=0 | | x+6y=-3 | | y=-2(5)+13 | | y=3/5x+2 | | -11*-11= | | 0=5x-25 | | 1/4x-2=7 | | 0.6x+0.2y=1.2 | | y=3/7x+8 | | -3x-20=43 | | y=-7/4x-3 | | 37c=777 | | y=7/5x+7 | | 2x-(4-2x)=-3(2-x) | | F(x)=2x^2-3x+1 | | f(x)=3(4)x-4 | | 3x-9=(-4) | | y=9/10x | | X(5x-15)=0 | | y=0.9x | | 0.5x-18=2 | | 4-7a=-24 | | F(x)=-2x^2+3x-1 | | 4-7a=24 | | y=-0.428x |

Equations solver categories